Using Models to Capture Patterns for Radically Increasing Social Impact - Williams, Andy (My University, 2022)
General Collective Intelligence is an emerging science that creates the possibility of exponentially increasing our general problem-solving ability and therefore our ability to solve any problem in general. This translates into significantly increasing social impact. One way of achieving this is defining patterns through which projects might be combined into networks of cooperation that increase impact on collectively targeted goals. In the case of the sustainable development goals, there are three patterns that together can be demonstrated to represent an exponentially greater number of potential solutions than currently available, and which can be demonstrated to have the potential for this exponentially greater impact. All of these patterns can be represented through domain specific models. This paper explores those models and how they might be leveraged to achieve this radically increased social impact.
Keywords: General Collective Intelligence; Human-Centric Functional Modeling; Model-Driven Engineering for Social Good